Structural Response of AISC- composite concrete filled circular steel Columns under Lateral Load - Sinan Abdulkhaleq Yaseen; Muhammed Ali Ihsan Saber; Bayan Salim Al-Numan (Zanco Journal of Pure and Applied Sciences, 2020)
In this article, there is a theoretical behavior research of composite frames consist of American Institute of Steel Construction (AISC)-composite pipes-filled with concrete to act as circular steel columns joined with steel beams subjected to unchanged axial loads and a lateral increasing load. The effects of column height and skin thickness, based on those available in the AISC manual, on the load-deformation reaction of composite frames, including steel tubes filled with concrete STFC, loaded by maximum vertical load allowed by AISC manual, were studied. A ANSYS program was used to develop a finite element (FE) model. This simulation considers linear and non-linear response of the composite materials. The obtained outcomes from the FE analysis were presented and discussed. Over the range of column heights (from 3048 mm to 6096 mm), no buckling has been reached and failure modes were observed after formation of plastic hinges at the connection of beam-column. For skin thicknesses (from 14.76 mm to 5.92 mm), varied load-deformation responses have been obtained. Stiffer Responses were obtained for skin thickness 14.76 mm. Lateral load range at failure was from 9.2 to 20.8 % of the maximum AISC vertical load, and displacement ductility was ranged from 1.71 to 3.08 for circular-STFC frames.